Ditch the Debate: Preparing Preservice Teachers to Nurture Productive Discourse About Controversial Issues - Kirk, Eric; Sadler, Troy D. (Innovations in Science Teacher Education, 2023)
This article showcases a lesson for preservice teachers designed to better prepare them in making instructional choices that support teaching and learning about complex socioscientific issues (SSI). Many of society’s most pressing social issues require the understanding and application of scientific knowledge. To do so, individuals must navigate not only the scientific dimensions of the issue, but also the moral considerations that arise from the application of scientific knowledge to these complex issues. We begin this article with a discussion of a framework for effective SSI-based teaching followed by a discussion of the unique challenges to teaching and learning that are posed by engaging students with complex, moral issues such as SSI. We then outline a lesson in which preservice teachers were exposed to two example SSI-based lessons. One lesson was designed to exacerbate challenges associated with engaging with morally fraught issues, whereas the other was designed to mitigate these challenges. Throughout this experience, students were encouraged to reflect on their experiences from their perspective as students and as developing teachers. This article concludes with recommendations for practitioners who may wish to implement this lesson, including suggestions for possible adaptations.